QP process for NORM waste transportation - Seif Al-Naimi (19772988) (2015)
Transportation of Naturally Occurring Radioactive Materials (NORM) Contaminated Waste in QP is carried out in accordance with the Radiation Protection Laws and QP Radiation Protection Standard for NORM Management (QP-STD-S-055). The QP Standard stipulates requirements for ensuring protection of persons and environmental from NORM impact, which is in line with the requirements of the Ministry of Environment (MoE) Resolution No. 45/2013, concerning the management of NORM Waste generated by Oil & Gas Industry in the State of Qatar. In addition, standard provides directions to all QP Operations, Contractors/Sub-Contractors and QP Join Venture companies (JVs) working within QP Premises on-shore and off-shore for identification, handling, transportation, storage and disposal of NORM Waste and related activities. Transportation of the NORM waste is carried out in accordance with the requirements as follows: The radiation level shall not exceed 5 µSv/h at the surface of each container of collected NORM waste. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.113